Applying Guided Reading Strategies to Improve Students’ Reading Comprehension of Descriptive Text - Elmiwati Elmiwati; Rona Elfiza; Inne Kusumawardhani (Badan Penerbit STIEPARI Press, 2025)
This research was held to improve the students’ ability in reading comprehension of descriptive text by using guided reading strategies. It was a Classroom Action Research which is consists 38 students. The data was collected by using task, test, observation checklist, interview and field note, and by using formula of mean score. The result indicate the students’ ability in reading comprehension of descriptive text improved in each cycle by using guided reading strategies. It can be seen from the mean score on the first cycle was 73,55 then improved in the second cycle was 82,37. Based on the result, the researcher concluded that the used of guided reading could improve students ability in reading comprehension of descriptive text.